Advances in Asthma Therapy with a Focus on Monoclonal Antibodies - Marcus Hesse (healthbook TIMES Das Schweizer Ärztejournal Journal Des Médecins Suisses)
Asthma can be well controlled in most patients with a basic therapy consisting of inhaled corticosteroids (ICS) and long-acting beta-agonists (LABA) or anticholinergics (LAMA). However, in some cases, severe asthma develops despite adequate therapy. Here, modern biologics, particularly monoclonal antibodies, can be used, targeting various pro-inflammatory factors. Targets would be IgE, IL-5, IL-4/IL-13 und thymus-stoma-lymphopoietin (TSLP).